Origin of the SN2 Benzylic Effect: Contributions by π Delocalization and Field/Inductive Effects - Rawlings, Robert E.; McKerlie, Adam K.; Bates, Daniel J.; Mo, Yirong; Karty, Joel M. (European journal of organic chemistry, 2012)
Historically, the SN2 benzylic effect is attributed to a conjugative stabilization between the phenyl ring and the reaction center in the transition state. However, recent papers have cast doubt on this explanation. We have therefore investigated the origin of the SN2 benzylic effect for two different gas‐phase SN2 reactions, F– + C6H5CH2F and Cl– + C6H5CH2Cl, by carrying out two separate computational methodologies on each system – a vinylogue extrapolation (VE) methodology and a block‐localized wavefunction (BLW) methodology. The contributions we examined were (1) delocalization involving the ring's π system, and (2) field/inductive effects of the ring. For the fluoride and chloride reactions, the VE methodology suggests that delocalization contributes to a lowering of the reaction's energy barrier by 3.1 and 1.7 kcal/mol, respectively, and the BLW calculations suggest that delocalization contributes to lowering the barrier by 3.65 and 5.47 kcal/mol, respectively. Both methodologies therefore agree that π delocalization is a significant contributor to the benzylic effect. Furthermore, the VE methodology indicates that field/inductive effects also contribute to lowering the barriers by 2.2 and 3.2 kcal/mol, suggesting that a separate repulsive interaction serves to increase the barrier by 1.5 and 3.3 kcal/mol, respectively. Recent publications have called into doubt π conjugation as the origin of the SN2 benzylic effect. In this computational study, we show that π conjugation does indeed have a significant contribution to the lowering of the gas‐phase SN2 energy barrier, as does a field/inductive effect by the phenyl ring.